2017
DOI: 10.1053/j.jrn.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Catabolism: A Possible Tool for Nutritional Monitoring of Patients With Acute Kidney Injury

Abstract: Hypercatabolism has been described as the main nutritional change in acute kidney injury. Catabolism may be defined as the excessive release of amino acids from skeletal muscle. Conditions such as fasting, inadequate nutritional support, renal replacement therapy, metabolic acidosis, and secretion of catabolic hormones are the main factors that affect protein catabolism. Given the imprecision of the methods conventionally used to assess and monitor the nutritional status of hospitalized patients, the parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Initially, urinary glucose excretion was significantly lower in DM-empa than in DM-cont rats, although the markedly higher Cglu in the DM-empa group resulted from the complete inhibition of glucose reabsorption, with FEglu being almost 100%. This finding was further supported by the significant reduction in urinary UN excretion, a parameter of protein catabolism, despite a normal BUN level, in the DM-empa group [ 37 ]. In addition, the increase in plasma TP and the decrease in urinary protein in the DM-empa group indicated that empagliflozin improved protein retention.…”
Section: Discussionmentioning
confidence: 78%
“…Initially, urinary glucose excretion was significantly lower in DM-empa than in DM-cont rats, although the markedly higher Cglu in the DM-empa group resulted from the complete inhibition of glucose reabsorption, with FEglu being almost 100%. This finding was further supported by the significant reduction in urinary UN excretion, a parameter of protein catabolism, despite a normal BUN level, in the DM-empa group [ 37 ]. In addition, the increase in plasma TP and the decrease in urinary protein in the DM-empa group indicated that empagliflozin improved protein retention.…”
Section: Discussionmentioning
confidence: 78%
“…PEW is prevalent in AKI patients and a meta-analysis of two studies reported that the prevalence of PEW in patients with AKI was 66.7% [8]. The pathogenesis of PEW in AKI is multifactorial, including metabolic alterations and impaired homeostasis responses due to sudden loss of kidney function [9], intrarenal and systemic inflammation associated with AKI [10], hypercatabolic state from the underlying comorbidity and critical illness [11], and amino acid loss in KRTs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Higher stages of AKI are often associated with higher risk of hypercatabolism. BUN may be evidence of hypercatabolism in severe AKI [ 29 ]. In multivariate Cox regression analysis, CRRT utilization was significantly associated with poor prognosis in patients with COVID-19 compared with the non-CRRT group.…”
Section: Discussionmentioning
confidence: 99%